CGIAR initiative examines the coherence of policies to help avert future food and water crises in Colombia - Villarino, Maria Eliza J.; Yomayuza, Karoll Valentina (Bioversity International and the International Center for Tropical Agriculture, 2022)
Illegal crops sprayed with chemicals that affect surrounding crops, rivers contaminated by the constant bombing of oil pipelines, forests cut down and converted into housing areas due to forced displacement and agricultural production— these are scenes repeated over the last five decades in Colombia. This is why issues surrounding the environment became central during the development and implementation of the peace agreement that the Colombian government and FARC guerrillas signed in 2016.